AN EXERGY COST ANALYSIS OF A COGENERATION PLANT - Gonçalves, L. P.; Arrieta, F. R. P. (Revista de Engenharia Térmica, 2010)
The exergy analysis, including the calculation of the unit exergetic cost of all flows of the cogeneration plant, was the main purpose of the thermoeconomic analysis of the STAG (STeam And Gas) combined cycle CHP (Combined Heat and Power) plant. The combined cycle cogeneration plant is composed of a GE10 gas turbine (11250 kW) coupled with a HRSG (Heat Recovery Steam Generator) and a condensing extraction steam turbine. The GateCycleTM Software was used for the modeling and simulation of the combined cycle CHP plant thermal scheme, and calculation of the thermodynamic properties of each flow (Mass Flow, Pressure, Temperature, Enthalpy). The entropy values for water and steam were obtained from the Steam Tab software while the entropy and exergy of the exhaust gases were calculated as instructed by. For the calculation of the unit exergetic cost was used the neguentropy and Structural Theory of Thermoeconomic. The GateCycleTM calculations results were exported to an Excel sheet to carry out the exergy analysis and the unit exergetic cost calculations with the thermoeconomic model that was created for matrix inversion solution. Several simulations were performed varying separately five important parameters: the Steam turbine exhaust pressure, the evaporator pinch point temperature, the steam turbine inlet temperature, Rankine cycle operating pressure and the stack gas temperature to determine their impact in the recovery cycle heat exchangers transfer area, power generation and unit exergetic cost.